Effects of felling Podocarpus glomeratus (Podocarpaceae) on the structure of Andean cloud forest (Cochabamba, Bolivia) - Ayma-Romay, Ariel Isaías (2009)
We examined the effect of logged mature trees on the structure, composition and natural regeneration of cloud forest. We installed 40 plots of 707 m2 measuring individuals >10 cm Dbh (Diameter at breast height), sub-parcels of 5 m2 for the regeneration <10cm Dbh and of 1 m2 for the seed-bank. We evaluated density and cover understory of all the trees. We did a cluster analysis for generating categories of cover canopy and also it makes principals components analysis (PCA) for determining the association of canopy cover with the density of different seedings species. The logging of mature trees modified the covering (p=<0,001) generating cano- pies different (few to strongly intervened). The canopy gaps improved the density of species shade-intolerant (Myrsine pseudocrenata, Vallea stipularis, Nectandra sp., Trichilia hirta, Miconia theaezans), some species shade-tolerant decreases their density sampling when decrease the covering canopy (Weinmannia microphylla, Condalia weberbaueri, Blepharocalix salicifolius and Styloceras columnare). The management of the forest has that maintain the understory cover of individuals >60 cm Dbh, to create areas protect in old forest and to promote practical of facilitating the growing of important trees.